Congoism Congo Discourses in the United States from 1800 to the Present - Van Hove, Johnny (transcript Verlag, 2017)
To justify the plundering of todays Democratic Republic of the Congo, U.S. intellectual elites have continuously produced dismissive Congo discourses. Tracing these discourses in great depth and breadth for the first time, Johnny Van Hove shows how U.S. intellectuals (and their influential European counterparts) have been using the Congo in similar fashions for their own goals. Analyzing intellectuals as diverse as W.E.B. Du Bois, Joseph Conrad, and David Van Reybrouck, the book offers a theorization of Central West Africa, a case study of normalized narratives on the »Other«, and a stirring wake up call for all contemporary writers on international history and politics.